The Big Entity of New RNA World: Long Non-Coding RNAs in Microvascular Complications of Diabetes - Raut, Satish K.; Khullar, Madhu (Frontiers in Endocrinology, 2018)
Abstract: A major part of the genome is known to be transcribed into non protein coding RNAs (ncRNAs), such as microRNA and long non coding RNA (lncRNA). The importance of ncRNAs is being increasingly recognised in physiological and pathological processes. LncRNAs are a novel class of ncRNAs that do not code for proteins and are important regulators of gene expression. In the past, these molecules were thought to be transcriptional ‘noise’ with low levels of evolutionary conservation. However, recent studies provide strong evidence indicating that lncRNAs are: i) regulated during various cellular processes, ii) exhibit cell type-specific expression, iii) localize to specific organelles and iv) are associated with human diseases. Emerging evidence indicates an aberrant expression of lncRNAs in diabetes and diabetes related microvascular complications. In the present review, we discuss the current state of knowledge of lncRNAs, their genesis from genome and the mechanism of action of individual lncRNAs in the pathogenesis of microvascular complications of diabetes and therapeutic approaches.